Effects of hydrocortisone and insulin on DNA internucleosomal fragmentation in rat thymocyte nuclei - A. V. Margaryan; I. G. Artsruni; K. S. Matinyan; E. S. Gevorgyan (ՀՀ ԳԱԱ հրատ.)
In the present work the effect of insulin and hydrocortisone on internucleosomal DNA fragmentation, the well known hallmark of apoptosis, in isolated rat thymocyte nuclei after 4 and 24 hours of hormones in vivo action has been examined. The changes of enzyme activity of poly(ADP-ribose) polymerase-1 (PARP-1) concomitantly were investigated. It was shown, that in 4 hours of hydrocortisone in vivo action no significant alterations of DNA oligonucleosomal fragmentation were observed. However, after 24 hours of steroid administration, sharp increase in fragmentation intensity and pattern were observed in thymocyte nuclei. Peptide hormone insulin had a different effect on DNA cleavage. In contrast to hydrocortisone, it significantly decreased the intensity of fragmentation in time-dependant manner. The data revealed that in 4 hour of both hormones action there were no changes in PARP-1 activity. Nevertheless, the activity of the enzyme declined about two-fold in 24 hours of hormones administration, which can probably reflect non-specific cell response upon hormonal stress. Ներկայացված աշխատանքում ուսումնասիրվել է ինսուլինի և հիդրոկորտիզոնի ազդեցությունը հորմոնների ներարկումից 4 և 24 ժամ հետո թիմոցիտների մեկուսացված կորիզներում ԴՆԹ-ի ինտերնուկլեոսոմային ֆրագմենտավորման վրա: Զուգահեռ ուսումնասիրվել է նաև հորմոնների ազդեցությունը պոլի(ԱԴՖ- ռիբոզ) պոլիմերազի (ՊԱՌՊ-1) ակտիվության վրա: Ստացված արդյունքները ցույց են տալիս, որ հիդրոկորտիզոնի in vivo ազդե ցությունից 4 ժամ հետո ԴՆԹ-ի ճեղքավորման զգալի փոփոխություններ տեղի չեն ունենում: Սակայն հորմոնի ներարկումից 24 ժամ հետո կտրուկ մեծանում է թիմոցիտների կորիզներում ԴՆԹ-ի օլիգոնուկլեոսոմային ճեղքավորման ինտենսիվությունը և փոխվում է բնույթը: Ինսուլինը ցուցաբերում է հիդրոկորտիզոնին հակադիր ազդեցություն: Կախված ինսուլինի in vivo ազդեցության տևողությունից, զգալիորեն ճնշվում է ԴՆԹ-ի ինտերնուկլեոսոմային ֆրագմենտավորումը: Արդյունքները վկայում են, որ հորմոնների in vivo ազդեցությունից 4 ժամ հետո կորիզներում ՊԱՌՊ-1-ի ակտիվությունը չի փոխվում, իսկ 24 ժամ հետո, ֆերմենտի ակտիվությունը նվազում է մոտ 2 անգամ, ինչը կարող է վկայել բջիջների հորմոնային սթրեսի նկատմամբ ոչ սպեցիֆիկ պատասխանի մասին: В представленной работе исследовано действие инсулина и гидрокортизона на интернуклеосомальное расщепление ДНК в изолированных ядрах тимоцитов через 4 и 24 ч после введения гормонов животным. Параллельно изучалось действие гормонов на активность поли(АДФ-рибоз)полимеразы 1 (ПАРП-1). Полученные результаты показывают, что заметных изменений в интернуклеосомальном расщеплении ДНК через 4 ч после инъекции гидрокортизона не происходит. Однако через 24 ч интенсивность олигонуклеосомального расщепления ДНК возрастает и меняется его характер. Инсулин проявляет действие, противоположное гидрокортизону. В зависимости от длительности in vivo действия инсулина интернуклеосомальное фрагментирование ДНК заметно подавляется. Итак, через 4 ч действия обоих гормонов активность ПАРП-1 в ядрах не меняется, а через 24 ч действия как одного, так и другого гормона активность фермента уменьшается в два раза, что может свидетельствовать о неспецифическом клеточном ответе на гормональный стресс.
Keywords: Biology; Cell Biology; Molecular Biology; Physiology